Integrasi Nilai Pendidikan Karakter dalam Pengembangan Kurikulum Berbasis KKNI untuk Perguruan Tinggi - Nuryanto (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2016)
Higher education has recently been required to implement the concept of national qualification framework of Indonesia (KKNI) in the instructional practices.This can be seen from the presidential regulation no 8 year of 2012 which states that KKNIisa staging qualification framework aimed at accommodating, balancing, and integrating between educational field and job training field and job experience as well. Meanwhile, the Constitution of National Education System No 20 year of 2003 briefly stating that “national education is to develop skill and build characters. Therefore, the higher educational institutions need to accommodate these two different goals. This article reviews literatures concerning on the essence of character values and how to adapt them into KKNI-based curriculum.